The Role of Student Team Heroic Leadership Strategy: Mathematical Communication of Middle-School Students - Muzaini, Muhammad; Rahayuningsih, Sri; Sirajuddin, Sirajuddin; Ikram, Muhammad; Hasby, Muhammad (Universitas Cokroaminoto Palopo, 2023)
The Role of Student Team Heroic Leadership Strategy: Mathematical Communication of Middle-School Students. Objectives: In this article, we focus on how to improve students’ mathematical communication in building effective group discussions using the student team's heroic leadership strategy. Methods: This type of research is Classroom Action Research, which was held in 2 cycles. The research subjects were 16 seventh-grade students (six boys and ten girls). Findings: The findings indicated that by implementing the Student Team Heroic Leadership learning strategy, students’ mathematical communication improved significantly. This finding is confirmed by the increase in the average score on students’ communication tests from 76% in cycle I to 96% in cycle II. The completeness criteria of the students’ mathematical communication exam results also progressed from the first to the second cycle. Other data indicate that students concealed information they did not comprehend during the learning process, making it harder for the teacher to assess their comprehension of the mathematical concepts provided. Conclusion: The study’s findings indicate that after using the Student Team Heroic Leadership learning strategy, students’ mathematics communication skills improved dramatically. As suggested, additional research should be able to examine ways to boost students’ self-confidence, particularly while displaying confusion when doing mathematical tasks provided by the teacher.